Educational teams: building professional and organizational learning communities - Pinheiro, Generosa; Alves, José Matias (Frontiers in Education, 2024)
Quality education that prepares young people to think and make ethically responsible decisions seems to be the only sustainable solution to respond to today’s global challenges. However, this capacity to learn requires a new school grammar, through the creation of conditions, structures and cultures that promote relationships and synergies capable of transforming teachers and school leaders into creative learners and facilitators of learning. In this sense, this study sought to understand the effects of a change in the organizational dynamics of a school, the organization of teaching by educational teams, on the individual, collective and organizational learning of this school organization. To this end, we adopted a fundamentally qualitative research approach, which we operationalized through a case study, based on a quali-quanti approach. We combined a descriptive statistical analysis of two questionnaires with a content analysis of interviews, focus discussion groups, and field notes from classroom observations and educational team meetings. The analysis of all these data points to the fact that effective change in schools and education that promotes deep learning for teachers and, consequently, for students and the organization, requires joint and articulated action not only at the level of structure and leadership, but also at the level of beliefs and school cultures.